2003
DOI: 10.1002/pmic.200390065
|View full text |Cite
|
Sign up to set email alerts
|

Stress protein flux during recovery from simulated ischemia: Induced heat shock protein 70 confers cytoprotection by suppressing JNK activation and inhibiting apoptotic cell death

Abstract: Multiple stress proteins are recruited in response to stress in living cells. There are limited reports in the literature analyzing multiple stress protein shifts and their functional consequences on stress response. Using two-dimensional electrophoresis we have analyzed shifts in stress protein profiles in response to energy deprivation as a model of ischemic injury to kidneys. A group of chaperones and stress-induced mitogen activated protein (MAP) kinases were analyzed. In addition to examining stress prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 41 publications
0
39
0
Order By: Relevance
“…A shift to the acidic end of the pH gradient (the left side of the gel) correlated directly with the level of protein phosphorylation. Therefore, protein at the basic end of the isoform string represents the unmodified form of the protein (14,16). This raises the question of functional differences between isoforms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A shift to the acidic end of the pH gradient (the left side of the gel) correlated directly with the level of protein phosphorylation. Therefore, protein at the basic end of the isoform string represents the unmodified form of the protein (14,16). This raises the question of functional differences between isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…The different spots corresponding to single protein species were found in all cases to correspond to the same molecular mass but possess slightly different isoelectric points. Because phosphorylation is known to occur in the ER (13)(14)(15)(16), these may represent different phosphoisoforms of the same protein. A shift to the acidic end of the pH gradient (the left side of the gel) correlated directly with the level of protein phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has been proposed that HSPs also act by means of a mechanism independent of Bcl-2, intervening at several points to halt progression of the apoptotic cascade (Strasser and Anderson 1995). Previous studies have indicated that at least some of the antiapoptotic activity of Hsp70 can be attributed to its ability to suppress the activity of JUN-kinase (Kumar and Tatu 2003;Gabai et al 1997). Activation of stress-activated protein kinase SAPK/c-Jun N-terminal kinase (JNK) has been strongly inhibited in cells in which Hsp70 was induced to a high level, indicating that Hsp70 blocks apoptosis by inhibiting signaling events upstream of SAPK/JNK activation.…”
Section: Heat Shock-induced Cell Protection From Apoptosis Inductionmentioning
confidence: 99%
“…Some of the anti-apoptotic activity of Hsp70 could be attributed to its ability to suppress the activity of JUN-kinase or Bid proteins [16,17] . Thus, the decreased activation of caspase-3 in the M3 treated group might be due to the inhibition of the JNK/Bim pathway by the induction of Hsp70.…”
Section: Discussionmentioning
confidence: 99%